Evaluation of psychological distress and fear among frontline hospital workers at COVID-19 centres in South East Nigeria - Bernadine N. Ekpenyong; Ekene M. Ani; Levi U. Osuagwu; Elvis Anyaehiechukwu Okolie; Miranda U. Ezema; Chundung A. Miner; Margaret I. Ojeahere; Margaret Akpan; Tanko Ishaya; Kingsley Agho; Christopher G. Piwuna (Discover Public Health)
Abstract Background Frontline hospital workers (FHWs) treating patients with COVID-19 during the pandemic have a greater risk of mental health problems. This study examined the prevalence of COVID-19-related psychological distress and fear among FHWs in South East Nigeria. Methodology A mixed-methods approach involving standardised quantitative tools and two focus group discussion sections with six participants each were used in this study. SPSS was used to analyse the quantitative data to produce descriptive and inferential statistics. Thematic analysis was used to analyse the qualitative data. Results A total of 603 (99.7%) FHWs responded out of 605 for the survey. The prevalence of psychological distress (65.0%, 392) and fear (68.2%, 411) was high. The multivariate analysis revealed that being aged 31–40 years (AOR = 1.78, 95% CI: 1.11–2.82, P = 0.016) and 51 years and above (AOR = 2.51, 95% CI: 0.99–6.33, P = 0.042) significantly increased the likelihood of experiencing psychological distress. Conversely, not having a previous history of psychological distress (AOR = 0.53, 95% CI: 0.36, 0.80, P = 0.004) was associated with a significantly lower likelihood of experiencing psychological distress. Nurses (AOR = 2.211; CI = 1.16, 4.23; P = 0.017), respondents with 3–4 years of practice experience (AOR = 2.068; CI = 1.20,3.57; P = 0.017) reported heightened fear. The qualitative findings revealed that high infection rates, media reports, high mortality, and poor adherence to preventive measures were risk factors for fear, while family and friends’ support, the use of Personal Protective Equipment (PPE), oath of practice, good working relationships, and management support were protective factors. Conclusion During the pandemic, FHWs in South East Nigeria experienced high levels of psychological distress and fear, especially those aged between 31 and 40 years, were male, and had previous experiences of distress. The qualitative findings provided valuable insights into risks and protections. This emphasises the urgent need to support the mental well-being of FHWs.